The effect of desmopressin on nocturnal polyuria, overnight weight loss, and morning postural hypotension in patients with autonomic failure. Issue 6543 (9th August 1986) - Mathias, C J; Fosbraey, P; da Costa, D F; Thornley, A; Bannister, R
Abstract : Day and night urine volume, morning and evening body weight, and supine and sitting blood pressure were measured in five patients with chronic autonomic failure who were not receiving treatment with drugs. All had nocturnal polyuria, overnight weight loss, and a pronounced postural fall in blood pressure, with lowest levels in the morning. Desmopressin (2-4 micrograms given intramuscularly at 8 pm) reduced nocturnal polyuria, diminished overnight weight loss, raised supine blood pressure, and reduced the postural fall, especially in the morning, when patients were often at their worst. Desmopressin may be a useful alternative to, or may supplement, other forms of treatment in some patients with autonomic failure.